Pengembangan Kriteria Status Mutu Ekosistem Danau Sebagai Bagian Dari Indikator Pengelolaan Terpadu Wilayah Sungai - Eko Winar Irianto; Robertus Wahyudi Triweko; Doddi Yudianto (JURNAL TEKNIK HIDRAULIK, 2010)
High rate of pollution on the watershed has impacted to deteriorate water quality reservoirs. Officially,Quality Status of Reservoir Ecosystem has not been established yet.So, this study describes theaccomplishment of integrated watershed management using Quality Status of Lake Ecosystem criteria(SMED) formulated by ministry of environment.The application of the criteria to Saguling and Sutamireservoirs datas shows that quality status of the reservoir ecosystems are in threat conditions.In order toapply the SMED criteria for assessment of quality ecosystem in reservoir, the advance experiments are stillneededmainlyfortheadditionalindicatorsasfollowing: 1)integrationbluealgaeandbiodiversityindicatorwith biodiversity index; 2) suitability of land erosion indicator connected with reservoir design of erosionrate; 3) shifting of siltation lake indicatorsiltation reservoir indicator in relation with the percentage ofdead storage volume; 4) integration hydroelectric power and water resources exploitation associated withthe hidrological reservoir and water balance; 5) suitability of fish cage calculation in reservoir, 6) suitability ofwaterqualityindicatorrelatedwithwaterqualitystandard;7)additionofcorrosivityindexandqualityofbottomsedimentinreservoir.TofacilitateapplytheSMEDfortheassessmentofreservoirecosystem.